Mahasiswa Peduli Stunting melalui Pendampingan Kegiatan Posyandu di Desa Pedamaran 1, Kabupaten Ogan Komering Ilir, Sumatera Selatan - Muhammad Nizar; Delia Yusfarani; S Sa’udah; Icha Damayanti; M Misnaniarti; Fatmalina Febry; Windi Indah Fajar Ningsih; Muhammad Amin Arigo Saci; Y Yeni; Laura Dwi Pratiwi (Jurnal TUNAS, 2023)
Stunting is a condition of failure to thrive and develops in children aged 0-59 months. Those whose length or height does not match their age due to chronic malnutrition and recurrent infections. One of the efforts made to prevent stunting in children aged 0-59 months is to disseminate information and education to parents of toddlers and pregnant women through posyandu. The purpose of this posyandu assistance is to identify the efforts of posyandu cadres in preventing stunting. The target population in this assistance were Posyandu Mawar 1, Mawar 2, Mawar 3, Mawar 4, and Mawar 5, 25 posyandu cadres, 1 village midwife, and posyandu visitors in Pedamaran I Village, Pedamaran District, Ogan Komering Ilir Regency, South Sumatra. The method used is PAR (Participatory Action Research) with qualitative descriptive analysis. It was carried out in several stages, namely observation, interviews, and household surveys. The result of this implementation is from posyandu assistance in preventing stunting posyandu cadres with village midwives carrying out various forms of activities besides measuring and weighing children's weight, socialize and education are also carried out for mothers who have children under five 0-59 months and pregnant women to recognize stunting and follow up on toddlers who are recorded as stunting.